The Male Peripubertal Phase as a Developmental Window for Reproductive Toxicology Studies - Elaine Perobelli, Juliana (Current Pharmaceutical Design, 2014)
The normal development of the male reproductive system can be divided into five phases: fetal, neonatal, childhood, puberty and adulthood. Childhood/peripuberty has yet been relatively little studied. Chemical insults during the peripubertal phase may result in adverse consequences that may be already visible during puberty as well as during later adult life. This occurs because endocrine disruptors often interfere in the developmental programming. The most important is to note that children are not just little adults and should be particularly investigated. The aim of this review is to discuss the recent literature (2000-2013) on male reproductive aspects in prepubertal toxicity assays, focusing on experimental in vivo studies, establishing a comparative analysis between the design, endpoints, results and consequent conclusion. The studies discussed in the present review were selected based on the period of exposure. Only studies with post-lactational exposures were included. 33 papers were included using rats, mice, rabbits or pigs as experimental model. There is a relative scarcity of studies investigating animals in development and thus an urgent need for further studies in order to evaluate the possible persistent effects on fertility and other reproductive parameters at adulthood. Another point is the lack of studies with chemical mixtures, an imminent problem in modern society. It is vital to consider the refinement of alternative methods and the experimental designs and endpoints to improve the scientific knowledge in this area.
Keywords: reproductive toxicology